Europe under Hitler : in prospect and in practice. (London New York Toronto Bombay Melbourne Cape Town : The Royal Institute of International Affairs Oxford University Press, 1941)
Bibliotheek Camille Huysmans
Overdruk uit: Bulletin of International News, 14 en 31 december 1940 en 25 januari 1941
Engels
Brochure
Keywords: Wereldoorlog 2